Imagining the university - Barnett, Ronald, 1947- (New studies in critical realism and education, 2013)
"Despite both positive and negative perceptions of the current state of higher education, the contemporary debate over what it is to be a university is limited. Most of all, it is limited imaginatively. The range of imagined options is narrow. The imagination has not been given anything even approaching a wide scope. As a result, our sense as to what a university could be and could become in the modern age is itself impoverished. If we are seriously to develop a wide range of ideas of the university that is adequate to the challenges of the modern world, the imagination itself needs to be freed. Imagining the University seeks to address each of these sets of issues and will do so by first, identifying a very wide range of ideas of the university as it is now unfolding and could become; secondly, by evaluating those conceptions of the university with a classification of ideas of the university; and thirdly, by reflecting on the imagination itself, its current impoverishment and its possibilities. Whether studying, researching or deciding policy, this book is vital reading to all those involved in the planning and delivery of higher education"--